Unveiling the Meaning of the Film Uang Panaik Maha(R)L: A Critical Discourse Analysis Approach - Nurfaedah, Nurfaedah; Bungatang, Bungatang; Ilma Rahim, Ilma Rahim; Sabata, Yusniati N.; Rosvita, Ita (Linguistics and ELT Journal, 2025)
This study aims to describe how the media represents the social conditions of the Bugis-Makassar ethnic community in South Sulawesi in the film Uang Panaik. This research uses a qualitative method with Critical Discourse Analysis (CDA), employing the Social Cognitive Approach by Teun A. Van Dijk. Teun A. Van Dijk's discourse theory consists of three categories: text, social cognition, and social context. The content of the text focuses on the screenplay of the film. Social cognition discusses the outcomes of the events depicted in the film. Afterward, it refers to the social context by illustrating the values of the society. The results of the study show that the critical discourse analysis of the film Uang Panaik Maha(R)L in terms of the text category includes macrostructure, superstructure, and microstructure. The social cognition category includes the creation of characters, language, and story conflicts. The social context category includes the representation of social phenomena, moral messages, and religious messages in the film Uang Panaik Maha(R)L.